Chrysippus' On affections : reconstruction and interpretations - Tieleman, Teun. (Philosophia Antiqua, 2003)
The 'On Affections' by the Stoic philosopher Chrysippus (c. 280-205 BCE) contains the classic exposition of the Stoic theory of the emotions. This book provides a fresh discussion of the extant evidence, id est the fragments and testimonies preserved by later sources. It aims to establish the exact amount of available evidence and to arrange the fragmentary material so as to see how far the original treatise can be reconstructed. The fragments are interpreted both in their literary context and in the light of Stoic doctrines known from other sources. Given its contextual approach, this study includes extensive discussion of the methods of sources such as Galen, Posidonius and Cicero. In addition, the medical backdrop to Chrysippus' theory receives considerable attention.